Implementation Chatbot on Whatsapp Using Artificial Intelligence With Natural Language Processing Method - Alia, Putri Ariatna; Febriana, Rusina Widha; Prayogo, Johan Suryo; Kriswibowo, Rony (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2024)
According to research conducted by we are social in 2023, internet users aged 16 - 64 years 92.1% use whatsapp as a long-distance communication medium. That this is the reason why business conversations switch to using whatsapp social media. In the business process, meetings between buyers and sellers are needed so that buyers can ask about the products they will buy before the goods are purchased by the buyer. Whatsapp is one of the solutions to this problem, but the meeting is virtual. The questions asked by several buyers about the items they want to buy are usually almost the same so the chatbot comes as a solution so that the seller does not have to answer repeatedly for the same questions asked by different buyers. Previous services used admin assistance to answer buyer questions, but this was considered less efficient because buyers could not receive answers to questions quickly, because the admin had another line of work, namely packing goods. Chattbot can answer questions in real time, so that buyers can receive information directly without waiting. The research method used is the Waterfall System Development Life Cycle (SDLC) which has four stages, namely analysis, design, coding and testing and uses the User Acceptance Testing (UAT) application testing technique. The results of the questionnaire sent to buyers stated that the service using the chatbot average index of 3.71.These results show the Chatbot system is very feasible and effective in helping customers obtain the information needed.